1998
DOI: 10.2134/agronj1998.00021962009000020003x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon Pools under Conventional and No‐Tillage Systems in the Argentine Rolling Pampa

Abstract: The Rolling Pampa is the most important cropping region of Argentina, and its soils are subjected to degradation. No‐tillage has been proposed to replace the use of the moldboard plow to reduce soil C losses. The effects of no‐tillage and plow tillage with and without N fertilization (0 or 90 kg N ha−1) on C inputs and outputs of a Typic Argiudoll and on organic C level and density fractions were studied in a field experiment at the end of 15 yr under a corn (Zea mays L.)‐wheat (Triticum aestivum L.)‐soybean [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(26 citation statements)
references
References 31 publications
4
19
0
2
Order By: Relevance
“…While C depletion can largely be explained by increasing cropping under conventional tillage, no-till not only seems to prevent C depletion but also to boost a long-term C gain in soils. This behavior can be confirmed through experimental results (Alvarez et al, 1999Alvarez, 2001;Chagas et al, 1995;Miglierina et al, 2000;Studdert and Echeverría, 2000).…”
Section: Across the Study Regionsupporting
confidence: 59%
“…While C depletion can largely be explained by increasing cropping under conventional tillage, no-till not only seems to prevent C depletion but also to boost a long-term C gain in soils. This behavior can be confirmed through experimental results (Alvarez et al, 1999Alvarez, 2001;Chagas et al, 1995;Miglierina et al, 2000;Studdert and Echeverría, 2000).…”
Section: Across the Study Regionsupporting
confidence: 59%
“…CO 2 flux from a non-tilled field was higher than from a tilled field in Argentina (Alvarez et al 1998) and slightly higher than from tilled fields in New Zealand (Aslam et al 2000) and Scotland (Vinten et al 2002). Alvarez et al (1998) reported from incubation experiments that the CO 2 flux was the same from soils with notillage and soils with tillage, and that the accumulation of labile organic matter caused a high CO 2 flux in the no-tillage treatment. In the NT treatment in our experiments, we hypothesize that the low input of labile organic matter because of the low biomass of maize and weeds resulted in a low CO 2 flux.…”
Section: Effects Of No-tillage Cultivation On Carbon Sequestrationmentioning
confidence: 97%
“…Aggregates physically protect SOM by (1) forming a physical barrier between microorganisms plus microbial enzymes and their substrates, (2) controlling food web interactions, and (3) influencing microbial turnover [97]. A closer look at the processes involved in aggregate formation and stabilization in temperate versus tropical soils illustrates the close relationship between soil biota and SOM dynamics.…”
Section: Model Of Interactions Between Aggregation and Biota Activitymentioning
confidence: 99%
“…9). This more pronounced aggregation increase does, however, not seem to lead to an [3,26,[30][31][32]35,38,59,65,77,79,109,111,113,114,139,164,172,173,177,194,Paustian and Elliott,unpublished,214,219,220,241] for (sub)tropical soils and from [2,11,22,42,50,[54][55][56]58,67,72,78,84,85,89,93,95,96,104,105,133,134,136,146,…”
Section: Mechanisms Of C Sequestration Under No-tillagementioning
confidence: 99%